2014
DOI: 10.1080/03630242.2014.932894
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Issues Among Pregnant Women in Correctional Facilities: A Systematic Review

Abstract: Incarceration-induced stress makes pregnant women in correctional facilities a high-risk group for mental health problems, resulting in adverse maternal and fetal outcomes. A systematic review was conducted to examine the prevalence and correlates of mental health issues among pregnant inmates. Databases searched included PubMed, Medline, CINAHL Plus, PsycINFO, National Criminal Justice Reference System, Social Work Abstracts, Cochrane and Campbell libraries, which were searched for studies published in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 42 publications
0
29
0
6
Order By: Relevance
“…Previous studies had already demonstrated worse social conditions 3,15,20,26 , the elevated prevalence of smoking 6,15,26,27 , alcohol and drug use 15,21,26,27 and mental disturbances 27 in incarcerated women.…”
Section: (16%) Strazza Etmentioning
confidence: 97%
“…Previous studies had already demonstrated worse social conditions 3,15,20,26 , the elevated prevalence of smoking 6,15,26,27 , alcohol and drug use 15,21,26,27 and mental disturbances 27 in incarcerated women.…”
Section: (16%) Strazza Etmentioning
confidence: 97%
“…In addition, a small number of studies have focused on psychiatric morbidity in prisoners at specialised mother and baby units 73…”
Section: Interventionsmentioning
confidence: 99%
“…Imprisonment during pregnancy may have negative impacts on the mental health and wellbeing of women, particularly for Indigenous mothers, as a consequence of being separated from family and country during their pregnancy [ 42 ]. There is evidence that maternal stress in pregnancy can impact on birth outcomes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%